(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A considerable change was noticed in the material life of north India around c. 600 B.C. Agriculture became the mainstay of the material life during this time. The settlements grew in the middle Gangetic basin. The topography and climate of this region together with technological innovations (use of iron) was responsible for agrarian prosperity in this region. This in turn had its reflection in the contemporary socio-political and economic life. The use of iron was at first restricted only in the manufacturing of weapons. The introduction of iron in the field of manufacturing weapon reflects the development in military machinery as well as the strengthening of the power of the ksatriyas.